2006
DOI: 10.1074/jbc.m607806200
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-response Genes Are Direct in Vivo Regulatory Targets of Brahma (SWI/SNF) Complex Function

Abstract: Metazoan SWI/SNF chromatin remodeling complexes exhibit ATP-dependent activation and repression of target genes. The Drosophila Brahma (SWI/SNF) complex subunits BRM and SNR1 are highly conserved with direct counterparts in yeast (SWI2/SNF2 and SNF5) and mammals (BRG1/hBRM and INI1/hSNF5). BRM encodes the catalytic ATPase required for chromatin remodeling and SNR1 is a regulatory subunit. Importantly, SNR1 mediates ATP-independent repression functions of the complex in cooperation with histone deacetylases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 65 publications
9
52
2
Order By: Relevance
“…In Drosophila, SWI/SNF has been shown to regulate hormoneresponsive ecdysone-induced genes (Schwartz et al, 2004;Zraly et al, 2006). In mammalian cells, the glucocorticoid receptor has been functionally linked to the SWI/SNF complex (Muchardt and Yaniv, 1993;Ostlund Farrants et al, 1997;Trotter and Archer, 2004), and the re-expression of either BRG1 or BRM is sufficient to restore glucocorticoid receptor function in cells that lack both BRG1 and BRM (Glaros et al, 2007).…”
Section: Brm and Brg1 Control The Expression Of Genes That Are Involvmentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila, SWI/SNF has been shown to regulate hormoneresponsive ecdysone-induced genes (Schwartz et al, 2004;Zraly et al, 2006). In mammalian cells, the glucocorticoid receptor has been functionally linked to the SWI/SNF complex (Muchardt and Yaniv, 1993;Ostlund Farrants et al, 1997;Trotter and Archer, 2004), and the re-expression of either BRG1 or BRM is sufficient to restore glucocorticoid receptor function in cells that lack both BRG1 and BRM (Glaros et al, 2007).…”
Section: Brm and Brg1 Control The Expression Of Genes That Are Involvmentioning
confidence: 99%
“…Although SWI/SNF is a relatively rare enzyme in yeast, present at only 100-500 copies per nucleus (Cote et al, 1994), it has been estimated that 5-7% of all yeast genes require SWI/SNF activity for expression (Sudarsanam et al, 2000;Zraly et al, 2006;Monahan et al, 2008). Estimates of the role of SWI/SNF in the control of Drosophila gene expression range from 1-2% of the genome (based upon inactivation of SNR1/ SNF5) to essentially the whole genome (based upon estimated chromosomal loss of RNA polymerase II in cells that express a dominant-negative brahma allele) (Armstrong et al, 2002).…”
mentioning
confidence: 99%
“…4E). Chromatin immunoprecipitation using whole animal extracts prepared from early pupae expressing HA-CMI and antibodies to the HA epitope revealed that CMI was strongly enriched at the endogenous Hsp27 EcRE, but not at another ecdysone inducible gene (Eig71Eh-i promoter) (Wright et al, 1996;Zraly et al, 2006) that lacks an EcRE, or at a control (rp49) gene. We conclude that CMI is a hormone-dependent co-activator of nuclear receptorstimulated transcription.…”
Section: Is a Nuclear Receptor Co-activatormentioning
confidence: 99%
“…and M.O.D., unpublished). To further our studies on epigenetic regulation of ecdysone target genes (Zraly et al, 2006), we searched for Drosophila genes that could encode a protein highly related to the N-terminal half of MLL2 and identified a single open reading frame (CG5591). We named the gene cara mitad (cmi; translated as 'dear half').…”
Section: Introductionmentioning
confidence: 99%
“…The developmental co-regulators of EcRs include TAIMAN (histone acetylase), 7 Trithorax-related (TRR) (histone lysine methyltransferase), 40 DART1 (histone arginine methyltransferases), 41 BRAHMA (ATP-dependent chromatin remodeler), 42 NURF (ATP-dependent chromatin remodeler), 43 and DEK (histone chaperone). 44 It will be interesting to examine whether these epigenetic factors, which influence EcR-mediated transcription in the nervous system during development, are likewise involved in transcriptional regulation in the nervous system in mature adult flies.…”
Section: Possible Involvement Of Chromatin Modifications In Ecdysone-mentioning
confidence: 99%